Making a life with words - Thomas, Kylie (PINS-Psychology in Society, 2016)
N Chabani Manganyi’s recently published memoir provides a chronicle of a life of contemplation, action and accomplishment under incredibly difficult circumstances. Manganyi is one of the most significant thinkers of his generation and the publication of this book is timely for a number of reasons.